PENGARUH COOPERATIVE PLAY TERHADAP KEMAMPUAN MOTORIK HALUS ANAK KELOMPOK BERMAIN NURUL HIDAYAH KECAMATAN TIKUNG KABUPATEN LAMONGAN - Mohammad Luthfillah (JCE (Journal of Childhood Education), 2020)
Motoric development is the process of a child learning to skillfully move the body. Children learn from the teacher about several movement patterns that can train dexterity, speed, strength, flexibility and accuracy of hand and eye coordination. cooperative play or a learning strategy to educate group cooperation and interaction between students. This study uses the form of Pre-Experimental Designs (Non designs) with the One Group Pretest-Posttest Design model, there are 19 respondents in this study and each child has the following different abilities with less fine motor skills than 9 children, while There are 8 children with sufficient fine motor skills, and 2 children with good fine motor skills. The validity used in this study is the validity of the construction. The purpose of this study (1) How is the Fine Motoric Ability of Nurul Hidayah Play Group Children, Tikung Lamongan?; (2) How is the effect of cooperative play on the Nurul Hidayah playgroup children, Tikung Lamongan district? the results of the pre-test score got a total score of 313 scores, while the posttest results got a total score of 403.The Wilcoxon Signed Rank Test test results also showed an influence in this learning, because the results of the calculation in the table obtained a value of 0.000 less than 0.05 (0.000 <0.05) then it was decided that Ho was rejected. It can be concluded that the cooperative play method affects the fine motor skills of children in the Nurul Hidayah Play Group, Tikung, Lamongan.